Prediction analysis of the length of time for changes in the status of positive patients for covid-19 delta and omicron variants using the markov chain model - Haryanto, Dwi; Addini, Fida Fathiyah (Universitas Islam Negeri Raden Intan Lampung, 2022)
In this research, a Markov chain model was constructed from the conditions that might be experienced by the people during the Delta or Omicron variant of the COVID-19 pandemic. This condition is divided into 3 states;